STUDY OF THE EFFECT OF PRELIMINARY PLASTIC DEFORMATION IN THE PROCESS OF DISSOLUTION DURING TEMPERING OF LOW-CARBON AND BORON-CONTAINING ALLOYS - Filonenko, M. Yu.; Piliaieva, S. B. (Science and Transport Progress, 2009)
In the paper the influence of preliminary deformation on disintegration of martensite in boron-containing and carbonic alloy is explored. It is shown that at the small degree of deformation (7 per cent) both in low-carbonic and boron-containing alloys the process of martensite disintegration takes place less intensively. The increase of degree of preliminary deformation in a boron-containing alloy is instrumental in more even distribution of boron-cementite particles appearing as a result of martensite disintegration.